AN ANALYSIS OF THE VISUAL AIDS USED IN THE STORY OF “LUCKY DAY” - Rakhimberdieva Ozoda (Journals Park Publishing, 2022)
The story of "Lucky Day" is one of the most popular stories in Korean literature. In 1924, Hyun Jingeon (1900-1943), a well-known realist writer of Korean literature, published the story "Good Luck". The work is written in the story genre and is based on the daily life of Kim Jong Un, the lowest stratum of the population during Japanese colonial rule. In fact, it was the most unfortunate day for the protagonist. This writer came up with a very witty title for the story. It would seem that a happy day, but turned out to be the most unfortunate day, but nevertheless he gave it the name "Happy Day". This title attracted readers so much that they had to keep reading to see how this happy day would develop.
Keywords: Poxon, flag samang; tokpap; irony